2019
DOI: 10.1021/acs.iecr.8b04543
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrothermal Aging on SO2 Poisoning over Cu-SSZ-13 Diesel Exhaust SCR Catalysts

Abstract: The impact of hydrothermal aging on SO2 poisoning over Cu-SSZ-13 selective catalytic reduction (SCR) catalysts were investigated in this study. The catalyst samples were hydrothermally aged at various temperatures for SO2 poisoning and characterized by SO2 temperature-programmed desorption (SO2-TPD), X-ray diffraction (XRD), H2 temperature-programmed reduction (H2-TPR), and NH3-TPD. The performance evaluations were also performed to illustrate the impact on SCR activity and oxidation. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
3
32
1
Order By: Relevance
“…Figure 7a shows the NO x conversion of fresh and sulfated Cu/SSZ-13 catalysts. Compared to F-Cu, the SCR activity of sulfated catalysts severely declined below 350 • C, but did not influence the NO x conversion at high temperature (above 350 • C), which agrees with other findings [25,38]. The SCR performance below 350 • C decreases as follows: F-Cu > S-Cu-0 > S-Cu-5 > S-Cu-10 > S- .…”
Section: Nh3-scr Reactions Over Cu/ssz-13supporting
confidence: 88%
See 1 more Smart Citation
“…Figure 7a shows the NO x conversion of fresh and sulfated Cu/SSZ-13 catalysts. Compared to F-Cu, the SCR activity of sulfated catalysts severely declined below 350 • C, but did not influence the NO x conversion at high temperature (above 350 • C), which agrees with other findings [25,38]. The SCR performance below 350 • C decreases as follows: F-Cu > S-Cu-0 > S-Cu-5 > S-Cu-10 > S- .…”
Section: Nh3-scr Reactions Over Cu/ssz-13supporting
confidence: 88%
“…Yasser et al [24] studied that SO 2 only adsorbed on Cu 2+ when ammonia was present and formed ammonium sulfate as the main poisoning route on this site, while, SO 2 could react with [Cu(OH)] + to form copper bisulfate. Wei et al [25] studied the impact of hydrothermal aging on SO 2 poisoning over Cu/SSZ-13. The authors found that copper sulfate species decreased when aging at 750 • C owing to copper migration and the contents of copper sulfate species increased at 850 • C aging as CuO x /CuAlO x species easy to react with SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon hydrothermal aging, Cu cations migrate through the CHA framework and it has been evidenced that ZCuOH is converted to the more stable Z2Cu [20,23,34] located in the 6-member rings. In particular, Wei et al [37] have demonstrated a decrease in sulfur storage and the mitigation of SO 2 poisoning on mildly hydrothermally aged (750 °C) Cu/SSZ-13. The conversion of ZCuOH to Z2Cu offers a greater resistance to SO 2 poisoning and an improved SCR efficiency at high temperature because ZCuOH is active for NH 3 oxidation.…”
Section: Drift Spectroscopymentioning
confidence: 99%
“…Selective catalytic reduction of NO with ammonia (NH 3 -SCR) has been widely used as one of the most effective technologies for the removal of nitrogen oxides from diesel engines. [1][2][3] Catalysts are the focus of the NH 3 -SCR reaction, on which many scholars have conducted extensive research. The NH 3 -SCR reactions are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur poisoning is due to the formation of the CuSO 4 -like species via the interaction of the isolated Cu 2 + species and sulfate, which reduced the active sites. [1] Cu-SSZ-13 has a certain tolerance to alkali metal poisoning when the content of alkali metal is below 0.50 mmol/gcat. As the alkali metal content increases, the catalyst deactivation becomes more and more serious, since the catalyst structure deteriorates severely and the amount of the isolated Cu 2 + species decreases sharply.…”
Section: Introductionmentioning
confidence: 99%